Reproductive Performance of Patients Undergoing Intracytoplasmic Sperm Injection with 100% Implantation Rate - Raziel, Arieh (Kluwer Academic Publishers-Plenum Publishers, 2000)
Purpose: To characterize the differences between twomatched groups of patients treated by ICSI: those pregnantafter all embryos transferred implanted (100% implantationrate) compared with nonpregnant patients. Methods: Twenty-one patients in whom one transferredembryo achieved a singleton pregnancy (group A) and 21pregnant patients to whom two or three embryos were transferredand achieved 11 twin and 10 triplet pregnancies(group B) compared with matched nonpregnant patients(group C and D, respectively). Results: The singleton pregnant patients were significantlyolder than the twin and triplet pregnancy patients. Althougha similar number of human menopausal gonadotropinampules were used in the singleton compared with the twinsand triplets a significantly lower number of oocytes andembryos were achieved at lower levels of estradiol on thehuman chorionic gonadotropin day in the former than inthe latter respectively. No difference was found between thepregnant women and their nonpregnant controls in any ofthe mentioned parameters. Good embryo morphology wasfound in 86% of the embryos in group A compared with62% in group C (P = 0.08) and 92% in group B comparedwith 66% in group D (P < 0.002). Conclusions: The only parameter in which pregnant patientswith 100% implantation rate differ from their nonpregnantcontrols was embryo quality.